The Impact of European Funds Upon the Tourism Development in Macroregion One from Romania - Marton BALOGH; Monica Maria COROŞ; Natalia NEGREA; Marius Emil COROŞ (Transylvanian Review of Administrative Sciences, 2010)
The present research paper comprises a review of the financing tools that were accessed both by the public administrations and by private enterprises from Macroregion One in Romania for tourism related activities. The authors’ attempt is to measure their efficiency by means of the tourist flows in the visited destinations. In its first part, our case study presents the current situation and the research methodology, while the last and most consistent part of the paper comprises the results obtained and discusses their implications and consequences. The last part of the paper highlights the conclusions that may be drawn given the findings of the undertaken research and analyses.